2012
DOI: 10.1007/s00122-012-1831-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of grain yield and physical grain quality in bread wheat (Triticum aestivum L.) under water-limited environments

Abstract: In the water-limited bread wheat production environment of southern Australia, large advances in grain yield have previously been achieved through the introduction and improved understanding of agronomic traits controlled by major genes, such as the semi-dwarf plant stature and photoperiod insensitivity. However, more recent yield increases have been achieved through incremental genetic advances, of which, breeders and researchers do not fully understand the underlying mechanism(s). A doubled haploid populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
96
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 41 publications
13
96
0
Order By: Relevance
“…On the same variant of fertilization 3N 2 (120 kg N ha -1 + 100kg P ha -1 ) other investigated wheat cultivar Lazarica achieved the highest yield (3724 kg ha -1 ). Grain per square meter were positively correlated with grain yield and influenced by kernels per spikelet, a measure of fertility (Bennett et al, 2012 Agropyrum repens L. Chenopodium album L. Chenopodium album L. The least grain yield was found on control variant for both of analyzed wheat cultivars Lazarica (1880kg ha -1 ) and Julija Mono (1740kg ha -1 ) tab. 3.…”
Section: Resultsmentioning
confidence: 97%
“…On the same variant of fertilization 3N 2 (120 kg N ha -1 + 100kg P ha -1 ) other investigated wheat cultivar Lazarica achieved the highest yield (3724 kg ha -1 ). Grain per square meter were positively correlated with grain yield and influenced by kernels per spikelet, a measure of fertility (Bennett et al, 2012 Agropyrum repens L. Chenopodium album L. Chenopodium album L. The least grain yield was found on control variant for both of analyzed wheat cultivars Lazarica (1880kg ha -1 ) and Julija Mono (1740kg ha -1 ) tab. 3.…”
Section: Resultsmentioning
confidence: 97%
“…In the Trident/Molineux population, the positive allele for grain yield on chromosome 4D came from Trident (Kuchel et al 2007). However, in the RAC875/ Kukri population, the positive allele in southern Australia came from RAC875 (Bennett et al 2012a), but in a heat environment in Mexico it came from Kukri (Bennett et al 2012b). Similarities to these interactions and effects were observed in our study (Tables 6 and 9), but clearly more work is required to determine the contribution of ALMT1 to the QTL effects observed in the Trident/Molineux and RAC875/Kukri populations.…”
Section: Effect Of Almt1mentioning
confidence: 98%
“…A rainfall/evaporation parameter was calculated by dividing growing-season rainfall by growing-season evaporation (Nidumolu et al 2012). Bennett et al (2012a) suggested that the proportion of rainfall received during the vegetative stage relative to growing-season rainfall might be important for classifying environments for wheat production in lower rainfall environments in southern Australia, so a rainfall ratio parameter was calculated as the ratio of rainfall between 1 April and 15 September to growingseason rainfall.…”
Section: Locations and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results on TKW seem to indicate that, under the drought stress conditions of Cd. Obregon (morning-dew environment), the plant tends to produce less numbers of grains per spikelet (and/or less tillers), maintaining grain size and density practically similar to that under the no-stress condition, while, under heat stress (but no water and N limitations), the plant tends to have a shorter grain filling period, reducing grain size and maintaining relatively high TW (Yang and Zhang, 2006; for a review; Bennett et al, 2012). Most cultivars showed practically no change in FP (97e105% of E1) under E2 and variable increases (4e16% higher than in E1) under E3, most likely related to the reduction in TKW observed in E3.…”
Section: Responses Of Genotypes and Parameters To Drought And Heat Stmentioning
confidence: 99%